Studi Kritis Sejarah Menyikapi Pluralitas Spiritualitas dari Persekutuan Doa Pietis dan Gereja Masehi Injili di Timor: Suatu Kajian Teologis-Historis - Rano Baki, Janter (Theologia in Loco, 2023)
The conflict between members of Prayer Fellowships and members of Gereja Masehi Injili di Timor because of differences in spirituality has become a struggle for the church, including its members in general. The relationship between the two tends to dominate each other. As a result, their relationship is strained. This article aims to find an alternative for GMIT to adequately manage the plurality of spirituality among its members amid the presence of the Prayer Groups. This article uses a theological approach combined with a historical phenomenology approach by Jan S. Aritonang. In the end, this article combines Joas Adiprasetya's model of the Garden and Tom Hovestol's Spiritual Profile to solve  the problem between GMIT members and Prayer Fellowship members. The Garden Model explains that believershave different ways to express their experiences, love, and relationships with the Triune God. While the Spiritual Profile offers a joint learning model based on Jesus' ministry, namely through koinonia and martyria. This article suggests that these two models give alternatives forGMIT in providing a common space for people with various spiritual practices to get to know each other's uniqueness through joint discussions about God's Word in-depth and learning spiritual discipline. The result is the manifestation of reciprocal openness and the restoration of tenuous relationships. These two alternatives can manage the plurality of spirituality in communion as a whole and in balance.